2019
DOI: 10.1016/j.ebiom.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of plasma miRNA biomarker signature panel for the detection of early HIV-1 infection

Abstract: Background Accurate laboratory diagnosis of HIV is essential to reduce the risk of HIV-positive individuals transmitting HIV-1 infection. The goal of this study was to identify and assess a panel of host derived plasma miRNAs that could to serve as a prognostic and predictive biomarker to detect early/acute HIV-1 infection. Methods A total of 372 microRNAs were analyzed in nine plasma samples from HIV-1 infected individuals in the early phase of infection and three heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 42 publications
(51 reference statements)
0
51
1
Order By: Relevance
“…In addition, silencing miR-21 was found to be correlated with an increased clinical outcome [45]. In contrast with our results, miR-16 has been reported to be upregulated in individuals with cHL [43,46] and also with miR-223 in HIV-1 individuals compared to healthy controls [61]. We found that these overexpressed levels are higher in HIV-infected individuals who have not developed cHL, suggesting possible repression of their expression in HIV-associated cHL.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, silencing miR-21 was found to be correlated with an increased clinical outcome [45]. In contrast with our results, miR-16 has been reported to be upregulated in individuals with cHL [43,46] and also with miR-223 in HIV-1 individuals compared to healthy controls [61]. We found that these overexpressed levels are higher in HIV-infected individuals who have not developed cHL, suggesting possible repression of their expression in HIV-associated cHL.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, MiR-16-5p has been linked with the pathogenesis of several infectious diseases such as HIV-1 infection and malaria [105107]. It is worth mentioning that miR-16-5p as a plasma diagnostic biomarker is able to distinguish severe and mild viral infections [108] and early HIV-1 infection from healthy individuals [106,109].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been identified as potential biomarkers of infections caused by a range of pathogens, including Hendra virus (Stewart et al, 2013), HIV (Biswas et al, 2019), tuberculosis (Zhang et al, 2013), malaria (Li et al, 2018), including differentiating complicated and uncomplicated P. vivax malaria (Kaur et al, 2018) and Ebola (Duy et al, 2016). In some studies, changes in miRNA profiles were observed early in disease onset, before the pathogen could be directly detected and prior to the onset of seroconversion (Stewart et al, 2013;Biswas et al, 2019). MicroRNAs have also been implicated in influenza infections (Scheller et al, 2019) and rhinoviruses (Hasegawa et al, 2018).…”
Section: The Potential For Mirnas To Improve Disease Outcomesmentioning
confidence: 99%
“…These miRNAs may be purely markers of viral exposure or may play a key role in HIV resistance. Recently, a panel of four miRNAs (miR-16-5p, -20b-5p, -195-5p, and -223-3p) was developed and tested for HIV diagnostic utility (Biswas et al, 2019). Blind testing was able to identify all positive samples and healthy controls with 100% sensitivity and specificity.…”
Section: Advantages Of Mirna Biomarkers I: Early Detectionmentioning
confidence: 99%